Sistema de numeração decimal : conhecimentos profissionais e práticas escolares de professores do 2º e 3º ano do 1º ciclo do ensino fundamental - Amaral, Elenir Honório do (2015)
This research aims to answer the question: “which are the professional knowledge about the Decimal Numeration System are manifested by teachers of the 2nd and 3rd grades of Elementary School and how they develop school practices related to this content in a city school of Cuiabá?”. The references that guide the investigation and the data analysis regularize themselves in the historic-cultural approach. To treat the foundations of historiccultural theory, we resort to the studies of Vygotsky (1988); Leontiev (1972); Rigon, Asbahr & Moretti (2010); Moura (2010) and other, Shulman (1986, 1987); Mizukami (2004) and other, about the professional knowledges; and Migueis & Azevedo (2007); Megid (2009); Nacarato et al (2011) and other, about the discussions of the mathematics in the early years. And, the historical aspects, theoretical-methodological and the school practices of SND we refer to Ifrah (2005); Boyer (1974); Lerner & Sadovsky (1996); Lanner de Moura (2007) and other. The research sets itself in a qualitative approach of case study, referred in Bogdan & Biklen (1994); Gonzáles Rey (2012); Stake (2010); André (1995) and other. Two teachers of the 2nd year and one of the 1st year of the Elementary School participated of the investigation. The sources of data are: characterization questionnaire, observation with record in a field diary, interviews and school documents. The data showed, in general, schooling experiences with little relevance in the access of construction/appropriation of mathematical knowledge and the process of professional formation, initial and continuing, as insufficient. That the absent of a proposal consolidated of collective pedagogical work and continuing formation in the school where they act, reflect in the actual practice and compromises the possibility of the teachers expanding their professional knowledge and promoting qualitative alterations in the process of teaching and learning of SND. We ascertain that, even though the pedagogical work of the teachers are different in some moments, their practices come close when teaching the SND without considering their genesis and history and the knowledge already elaborated by the students, they do not motivate the interaction between students and, also, the pedagogical mediation characterize itself by the collective orientation about the procedures to be adopted to the resolution of the proposed exercises. The teaching of SND is done, generally, through the emphasis of the names of the units of order, when the realization of numerical operations through conventional algorithms, without returning and promoting reflections with the students about the rules and properties of SND, underlying operations. We found that there are some blanks in the specific and curricular knowledge of the teachers, specially, about the comprehension of the base ten and positional value of algorithms and knowledge of the proposal approaches of SND presents in the official curricular references, which reverberates in how they develop the teaching of this content. The analysis of data also takes us to consider that the teaching of SND should consider the history and the creation of the concept from problem situations that allow to the teachers and students to live them as protagonists and not as mere transmitters and viewers. So the teacher needs to have objective work conditions and the initial and continuing formation need to be rethought